Analysis Of Financial Performance In Makmur Cahaya Semesta Company - Hira Sulfiana; Malahayatie; Trie nadilla; Lia Safrina (CV. Era Digital Nusantara, 2024)
The purpose of this study was to analyze the Financial Performance of PT. Makmur Cahaya Semesta Banda Aceh Period 2020-2023. The method used is descriptive quantitative analysis with calculations using financial ratios. The results showed that the liquidity ratio showed that the company's financial condition in meeting its financials was running very well, the solvency ratio showed that the company experienced instability due to little capital compared to its total debt so that it was said to be unsolvable, the activity ratio showed that the turnover of business assets and fixed assets experienced stability, the profitability ratio increased every year, and the growth ratio experienced a significant decline. Based on this, it can be concluded that the liquidity ratio, profitability ratio and activity ratio are in good condition while the solvency ratio and growth ratio are in bad condition.